2012
DOI: 10.1002/clen.201000472
|View full text |Cite
|
Sign up to set email alerts
|

Bioremediation of Phenanthrene by Mycoplana sp. MVMB2 Isolated from Contaminated Soil

Abstract: Bioremediation of Phenanthrene by Mycoplana sp. MVMB2 Isolated from Contaminated SoilThe effect of nutrient and surfactant addition on the biodegradation of phenanthrene was studied in a batch scale soil-slurry system using isolated Mycoplana sp. MVMB2strain. The study was conducted using an artificially phenanthrene spiked and as well as contaminated soil from petrochemical industrial site. Maximum phenanthrene degradation and subsequent high microbial growth were observed at optimum pH (pH 6) and C/N/P ratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…An indigenous microbial community involved in the degradation of PAHs already exists in contaminated soils and the microorganisms have adapted and acclimatized to PAHs degradation. Several authors reported a wide variety of bacteria capable of metabolizing PAHs including the genera Acidovorax , Acinetobacter , Aeromonas , Alcaligenes , Arthrobacter , Beijerinckia , Brevibacterium , Flavobacterium , Micrococcus , Mycobacterium , Mycoplana , Nocardia , Pseudomonas , Rhodococcus , Sphingomonas , Streptomyces , Vibrio , etc.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…An indigenous microbial community involved in the degradation of PAHs already exists in contaminated soils and the microorganisms have adapted and acclimatized to PAHs degradation. Several authors reported a wide variety of bacteria capable of metabolizing PAHs including the genera Acidovorax , Acinetobacter , Aeromonas , Alcaligenes , Arthrobacter , Beijerinckia , Brevibacterium , Flavobacterium , Micrococcus , Mycobacterium , Mycoplana , Nocardia , Pseudomonas , Rhodococcus , Sphingomonas , Streptomyces , Vibrio , etc.…”
Section: Discussionmentioning
confidence: 99%
“…Several authors reported a wide variety of bacteria capable of metabolizing PAHs including the genera Acidovorax , Acinetobacter , Aeromonas , Alcaligenes , Arthrobacter , Beijerinckia , Brevibacterium , Flavobacterium , Micrococcus , Mycobacterium , Mycoplana , Nocardia , Pseudomonas , Rhodococcus , Sphingomonas , Streptomyces , Vibrio , etc. .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A DNA-based and stable isotope probing (SIP) study with [U- 13 C]anthraquinone from PAH-contaminated soil showed that the genus Phenylobacterium is responsible for anthraquinone degradation 43 . The genus Mycoplana is also known to degrade aromatic hydrocarbons 44,45 . Our observations are corroborated by petroleum hydrocarbon analysis, which revealed that short-chain alkanes (C 15 ) and relatively low-molecular weight PAHs such as naphthalene were rapidly depleted over the first ~100 days when populations of early responders were enriched 32 .
Figure 5Relative abundance of taxa detected at the genus level in SOAs (solid) and uncontaminated control sands (dotted) over the 3-year time course.
…”
Section: Resultsmentioning
confidence: 99%